Critical factors of quality management used in research questionnaires : a review of literature - Kanagi Kanapathy, * (Sunway University College, 2008)
This paper examines the emergence of critical factors of quality management in the development of quality management research questionnaires. A review of literature shows that 27 different critical factors or constructs were developed and used by established researchers in the field. Out of these, 8 most popular critical factors have been identified ? top management support, quality information availability, quality information usage, employee training, employee involvement, product?process design, supplier quality and customer orientation. This paper suggests that the critical factors of quality management be standardized so that a sound comparison can be made between research findings of studies conducted in various countries of the world.